2018
DOI: 10.1016/j.ijhydene.2018.03.159
|View full text |Cite
|
Sign up to set email alerts
|

Deflagrations of localised homogeneous and inhomogeneous hydrogen-air mixtures in enclosures

Abstract: Two original models for use as novel tools for the design of hydrogen-air deflagration mitigation systems for equipment and enclosures are presented. The first model describes deflagrations of localised hydrogen-air mixtures in a closed space such as a pressure vessel or a well-sealed building while the second model defines safety requirements for vented deflagrations of localised mixtures in an enclosure. Examples of localised mixtures include 'pockets' of gas within an enclosure as well as stratified gas dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The contribution of hydrogen combustion to maximum pressure beyond this concentration range can be neglected. This assumption is in line with the conclusions of the study [18], where it was observed that only a small fraction of a non-uniform hydrogen-air mixture with burning velocity within the narrow range of 95-100% of the maximum value of burning velocity within a vented enclosure defines the maximum vented deflagration overpressure.…”
Section: The Similitude Analysissupporting
confidence: 90%
“…The contribution of hydrogen combustion to maximum pressure beyond this concentration range can be neglected. This assumption is in line with the conclusions of the study [18], where it was observed that only a small fraction of a non-uniform hydrogen-air mixture with burning velocity within the narrow range of 95-100% of the maximum value of burning velocity within a vented enclosure defines the maximum vented deflagration overpressure.…”
Section: The Similitude Analysissupporting
confidence: 90%
“…Hence this study focuses on gas detectability rather than explosion risk, which is an important topic in its own right and is being actively investigated (e.g. Sinha et al, 2019;Lowesmith et al, 2009, Makarov et al, 2018. ISO 13734:2013 presents the general characteristics of an effective odorant:…”
Section: Odorisation Practices In the Ukmentioning
confidence: 99%
“…No theoretical foundation has been given for this formulation of the DOI number and it appears to be of empirical nature. useful extension of this model is also proposed recently [37] which deals with the case of stratified fuel distribution.…”
Section: Molkov and Bragin Model (2015) -This Modelmentioning
confidence: 99%